Méthodes pédagogiques pour l’enseignement interculturel à travers le manuel Super Français au SMAN 2 Ungaran - Cindy Putri Varadela; Sri Handayani (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
The teaching method is a way that will be applied to students to provide information about the learning material. The use of learning methods will make it easier for teachers to teach learning materials in class. In connection with the learning methods that implement the independent curriculum, there are several student-centered learning methods. The purpose of this study is to describe the methods used by teachers in teaching intercultural knowledge through Super Français textbooks in class XI SMA N 2 Ungaran and to describe the obstacles experienced by teachers in preparing intercultural teaching. This research uses a descriptive qualitative approach. The respondents in this study were teachers and grade XI students studying French at SMA N 2 Ungaran. To collect data, we used observation and interview techniques. The data obtained was analyzed using descriptive analysis. The results of this study are about the methods used by teachers in teaching French cross-cultural knowledge at SMA N 2 Ungaran are discussion methods, simulation methods, computer-assisted learning methods (CIA Computer Assisted Learning) and assignment methods and there are obstacles felt by teachers in preparing intercultural teaching.